Kualitas Pelayanan dan Kepuasan Pasien (Studi Kasus Instalasi Laboratorium Rumah Sakit ST. Theresia Jambi) - Ubaidillah Ubaidillah (Universitas Batanghari Jambi, 2021)
The purpose of this study is to see the extent to which service quality affects patient satisfaction, the subjects used as the unit of analysis in this study are patients who use the services of the ST hospital laboratory installation. Theresia Jambi, totaling 57 patients, the data collection technique used a closed questionnaire given to respondents with alternative answers that had been provided, then the data was processed using regression analysis. The results of this study prove that the higher the level of service quality provided, it can affect the increase in patient satisfaction.